Food price inflation and the poor - Ngidi, Bandile (My University, 2016)
Food price inflation has been an important subject of debate internationally since 2008. This sharp increase in food prices experienced during 2008 lead to intense research into the causes, dynamics and responses to this particular instance of food price inflation. The international literature attributed food price inflation to such factors as climate change, increases in energy costs and speculative activity in financial markets for agricultural commodities. This research report undertakes a review of the measurement of food price inflation in South Africa, broadly assessing how it is to be linked to the poor in South Africa. The research report focuses on the work of institutions concerned with the measurement of food price inflation in South Africa. Different methodologies of identifying foods as food staples are looked at. Food prices and trends are analysed using CPI data from January 2008 until October 2008, using selected consumer price index series from Statistics South Africa. The research report finds that the institutions studied show evidence of that higher food price inflation is correlated with demographic markers of poverty, although the traditional measure, the CPI, does not suggests that this is very extensive. This, it is argued, is due to the calculation methodologies used in the published CPI, and the data period. The research report then ends with an overview of the political economy of food in South Africa, thereby makes recommendations as to why the measurement of food price inflation is important for the poor.
Thesis (M.Com. (Development Theory and Policy))--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Economic and Business Sciences, 2015.
Keywords: Poor--South Africa; Inflation (Finance)--South Africa; Consumer price indexes--South Africa.